The Concept of Mass Media and Its Current Significance and Its Other Disadvantages and Advantages Sides - Musaeva G.I. (Genius Journals, 2021)
This article is about how social networks, including Facebook, Twitter, Instagram, YouTube, Tumblr, and the like - allow anyone in the world to post what they want - truth or falsehood - with very little control or censorship. data are given. This has led to the widespread use of “bots” - computers - that millions of fake, almost always inflammatory, real people, even real people, have posted on these social media apps as well-known friends. This significantly shifts public opinion to extremes, such as in the U.S., forcing conservatives to think liberals are really worse and liberals to think the opposite. At the same time, the analysis of general information about the mass media is mentioned.
Keywords: Mass media; Facebook; Twitter; Instagram